Analisa visual karya berbentuk realisme melalui kajian perbandingan terhadap beberapa artis terpilih - Mohd Syakir, Razak (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This research is a comparative analysis of selected references artist namely Dirk Dzimirsky, Diego Fazio and Mike Clapton especially on the study about emotions and dramatic expression. The researchers has applied the aspects of composition, lighting, techniques and ideas based on the artists and the researcher had use all these features in producing personal artworks. In this research, the method of practice-based has been applied before a comparative study has been carried out to obtain the information espeacially on the techniques and approaches used by the artists before researchers apply all these findings into a personal artwork.